Fertility preservation in a transgender man without prolonged discontinuation of testosterone: a case report and literature review - Kristy Cho, M.D; Rahana Harjee, M.D; Jeffrey Roberts, M.D; Caitlin Dunne, M.D (Elsevier, 2020)
Objective: To study the feasibility of fertility preservation in a transgender man without an extended period of androgen cessation. Design: Report of a foundational case of oocyte cryopreservation in a transgender man without stopping testosterone therapy before controlled ovarian stimulation. We performed a literature review, identifying five publications on oocyte cryopreservation outcomes in transgender men on testosterone. Setting: A university-affiliated fertility clinic in Canada. Patient(s): A 28-year-old transgender man taking testosterone for 3 years requesting oocyte cryopreservation before gender-affirming surgery. He desired to proceed without stopping testosterone. Pretreatment antimüllerian hormone level was 1.89 ng/mL. The patient's consent was obtained for written publication. Intervention(s): Testosterone was stopped for only three doses (immediately before and during ovarian stimulation). A standard antagonist protocol was used with letrozole to minimize estrogenic side effects. Main Outcome Measure(s): Number of oocytes retrieved and days off testosterone. Result(s): Thirteen oocytes were retrieved; 11 were mature and vitrified. The total time off testosterone was 24 days. In all prior publications, testosterone was stopped for 3-6 months. Conclusion(s): Transgender men have traditionally discontinued exogenous testosterone until the resumption of menses (≤6 months). This is known to be distressing. This is the first published case demonstrating the feasibility of ovarian stimulation without prolonged testosterone cessation in a transgender man. Future studies with a larger sample size should be performed to confirm these findings. The short duration off testosterone may improve patient's experiences, increase treatment acceptability, and decrease gender dysphoria for transgender men considering fertility preservation.